An Analysis of Pakistan Television Corporation Entertainment Programs and its Effects on Youth - Amin , Salman; Juni , Muhammad Sher; Ali, Asghar (Asian Journal of Empirical Research, 2014)
This study has been conducted to examine and indicate the consumption patterns of Pakistan Television Corporation (PTV) entertainment programs of rural viewers of Karor Lal Eason (Layyah). For this study 200 respondents are selected which equally consist 100 males and 100 females. The findings indicated that the viewers prefer to watch PTV entertainment programs and they also spend maximum time on watching entertainment programs of PTV. It is indicated that most of the respondents prefer to watch the PTV entertainment programs during prime time. Findings further indicated that female viewers change their working time to watch their favorite programs which includes dramas. Findings show that most of the respondents express their views that PTV entertainment programs are promoting new cultural trends in our rural society. The findings reveal that most of the respondents are agree the PTV entertainment programs are helpful for them to adopt new cultural trends, in the same way it is the perception of overall respondents that new cultural trends presented in the PTV entertainment programs should come to our traditional society.